RELATIONS AND DEVELOPMENT OF THE DABUSIYA FORTRESS ON THE GREAT SILK ROAD WITH NEIGHBORING CITIES (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Abstract. This article discusses Dabusiya fortress and its neighboring cities on the Great Silk Road, and considers the specific aspects of the cities.